1985
DOI: 10.3171/jns.1985.62.3.0425
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparesis caused by vertebral artery compression of the medulla oblongata

Abstract: The case is reported of a patient with progressive left hemiparesis due to vascular compression of the medulla oblongata. Metrizamide computerized tomography cisternography revealed that the left vertebral artery was compressing and distorting the left lateral surface of the medulla. Compression was surgically relieved and symptoms improved postoperatively. Neurological and symptomatic considerations are discussed in relation to the topographical anatomy of the lateral corticospinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…2) Placement of a prosthesis between the artery and spinal cord is another procedure to reduce vascular decompression and is currently the preferred treatment for hemifacial spasm and trigeminal neuralgia. 4) However, this method does not ensure decompression of the cervical cord because the offending vessels are large, and so the symptoms may progress postoperatively. We emphasize that mobilization of the artery and anchoring to the dura is probably the most effective treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Placement of a prosthesis between the artery and spinal cord is another procedure to reduce vascular decompression and is currently the preferred treatment for hemifacial spasm and trigeminal neuralgia. 4) However, this method does not ensure decompression of the cervical cord because the offending vessels are large, and so the symptoms may progress postoperatively. We emphasize that mobilization of the artery and anchoring to the dura is probably the most effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Neurovascular compression of the medulla oblongata can cause hemiparesis, 3,4) which may be associated with hypertension. However, cervical myelopathy caused by neurovascular compression is rare, with only five cases of cervical myelopathy due to vascular compression of the upper cervical spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Levine et al previously reviewed literature and showed that in 128 patients, 58% experienced cranial nerve compression, most of them complaining about facial spasm and trigeminal neuralgia, 48% experienced vertebrobasilar insufficiency or stroke or both, 31% had hydrocephalus and only 24% had symptoms and signs from brain-stem compression 16 . Kim et al, in 1985, were the first to report brainstem dysfunction caused by vascular compression 17 . Experimental studies have shown that rapid mechanical compression of the brainstem induces immediate damage, and this is directly proportional to the degree of compression.…”
Section: Discussionmentioning
confidence: 99%
“…Tortuosity of the VA, in particular, has been shown to produce extradural cervical radiculopathy as well as intradural brainstem dysfunction by direct compression. 1,6,7,[9][10][11][12][13][17][18][19][20]23,25,29,30 Such tortuosity has been observed postmortem in anatomical studies, as well as in vivo on radiography, MRI, or via traditional angiography. 2,5,28,35 Classically, Jannetta linked vascular compression of the trigeminal nerve to trigeminal neuralgia, and showed that microvascular decompression of the affected nerve could produce symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%